A Model for Calculating Interconnection Costs in Telecommunications - Um, Paul Noumba; Gille, Laurent; Simon, Lucile; Rudelle, Christophe (Washington, DC: World Bank and the Public–Private Infrastructure Advisory Facility, 2013)
Since the past decade, several Sub-Saharan African governments, through technical assistance provided by the World Bank and other donors, have undertaken to reform their telecommunications sectors, by implementing market liberalization policies, privatizing the incumbent public operator, and creating autonomous and independent regulatory bodies. The core objective of these reforms is to significantly improve access, and affordability, to telecommunications services on the basis of the assumption that a more friendly and predictable business environment will attract more private investment. However, the provision of interconnection services, on fair and efficient terms, has rapidly emerged as a main bottleneck. In fact, new legislation and regulations enacted in Sub-Saharan Africa recognize the interconnection rights ascribed to all telecommunications service providers and network operators. In addition, these regulations also request the incumbent fixed operator to supply interconnection services to new entrants on a fair and competitive basis. Despite the clarity and soundness of the legislative provisions in that respect (cost oriented, nondiscriminatory, fair, and transparent), the number of interconnection disputes has increased, and long-lasting interconnection disputes have discredited the reputation and credibility of new regulatory regimes.